Use of Bacillus velezensis JNS-1 from vermicompost against strawberry root rot - Jiang, Lili; Yan, Haohao; Yin, Yingzi; Dong, Ran; Wu, Chong (Frontiers in Microbiology, 2025)
China is the biggest producer of strawberry and has the largest strawberry cultivation area worldwide. This study adopted an experimental method to explore the effect of vermicompost addition on the yield and quality of strawberries and to investigate the influence of the composition and activity of microbial communities in soilless cultivation systems. The addition of vermicompost significantly increased the activity of three soil enzymes, namely cellulase, urease, and acid phosphatase. Furthermore, it significantly increased the nitrogen content of the strawberry-planted substrate, through NO3-N and alkaline-N contents and organic matter, as well as the available-K content and cation exchange capacity, but with no significant effect on the available-P content of the substrate. Vermicompost addition effectively improved the growth of strawberry plants by transforming microbial diversity and increasing the level of beneficial microbial transcription. The average plant yield of the first-crop fruit of vermicompost-treated plants was significantly higher than that of the control. Furthermore, a biocontrol strain named JNS-1 was isolated from the vermicompost, which showed a good direct inhibitory effect against the mycelial growth of Fusarium oxysporum and Neopestalotiopsis spp. According to its morphology and 16S rRNA gene sequences, JNS-1 strain was identified as Bacillus velezensis. In greenhouse pot experiments and field trials, B. velezensis JNS-1 was found to be effective in controlling strawberry root rot disease. This study focuses on using B. velezensis JNS-1 to enhance the health and quality of strawberries and providing a theoretical basis for the use of B. velezensis JNS-1 in strawberry fields.